Crystal Structure of 4-[(2-hydroxy-3-methoxybenzyl)amino]benzoic Acid Hemihydrate - Kamaal, S.; Faizi, M.S.H.; Ali, A.; Ahmad, M.; Gupta, M.; Dege, N.; Iskenderov, T. (International Union of Crystallography 5 Abbey Square Chester CH1 2HU, 2019)
In the crystal of the title vanilline derivative, 2C 15 H 15 NO 4 ·H 2 O, the secondary amine molecule is accompanied by half equivalent of water. The molecule is non-planar, with torsion angle C aryl - CH 2 - NH - C aryl of -83.9 (2)°. In the crystal, the system of O - H⋯O hydrogen bonds, including bridging water molecules residing on crystallographic twofold axes, results in a two-dimensional layered structure. Within the layers, there are also weak N - H⋯π interactions involving the vanilline benzene ring. © Kamaal et al. 2019.
Keywords: 2-Hydroxy-3-Methoxy-Benzaldehyde; 4-Aminobenzoic Acid (PABA); Crystal Structure; Hydrogen Bonding; Secondary Amine; Vanillin